Recurrence of borderline ovarian tumors - Svintsitskiy, V.S.; Vorobyova, L.I.; Klymenko, E.S.; Dermenzhy, T.V.; Tkalya, J.G. (Experimental Oncology, 2013)
Aim - to increase the efficiency of diagnosis and treatment of patients with recurrences of borderline ovarian tumors (BOT). 106 patients with BOT of stage I have been treated and clinically observed: the I group (82 patients, mean age - 38,9 +- 5,5 years), who were treated with standard surgical operation (panhysterectomy); the II group (24 patients, mean age - 30,3 +- 5,5 years), who underwent preserving surgery. The main method of treatment of patients with BOT is surgical. For patients of older age effective extension is panhysterectomy with the greater omentum resection. Further chemotherapy can be applied as the second stage of complex treatment in case of confounding factor of prognosis. Preserving treatment does not aggravate the indices of the survival rate among patients with BOT, which is confirmed by results of 5- and 10-years survival rate among patients after the preserving (I group) and standard surgery (II group): 87,4 and 79,2 % in the I group respectively, and 80,1 and 72,3 % in the II group respectively. The frequency of recurrence is higher in cases of bilateral affection of ovaries (IB stage), collapse of a capsule prior to the surgery. Sonography is a highly informative method of diagnostics of BOT relapse with its sensitivity 83,5 %, specifity - 64 %, favorable prognostic possibility - 56 %, unfavorable prognostic possibility - 66,4 %.